An oxic/anoxic-integrated and Fe/C micro-electrolysis-mediated vertical constructed wetland for decentralized low-carbon greywater treatment. (November 2020) - Deng, Shihai; Xie, Binghan; Kong, Qiang; Peng, Shuai; Wang, Hengchen; Hu, Zhifeng; Li, Desheng
Graphical abstract: Highlights: Oxic/anoxic and micro-electrolysis integrated constructed wetland was developed. Decentralized low-carbon greywater was treated at ambient temperature −11.5 to 8.0 °C. High NH4 + -N (94%), TN (86%), TP (98%) and COD (93%) removals were achieved. Micro-electrolysis-produced H2 /Fe 2+ mediated denitrification and dephosphorization. AOB, NOB, autotrophic denitrifier and Fe II -oxidizing bacteria dominated the system. Abstract: The treatment of decentralized low-carbon greywater in rural area, particularly in cold weather, remains a challenge. Oxic/anoxic process and Fe/C micro-electrolysis were incorporated into vertical constructed wetland to develop ME-(O/A)CW for practical decentralized low-carbon greywater treatment. ME-(O/A)CW provided NH4 + -N, TN, TP and COD removal of 94.3%, 86.2%, 98.0% and 92.7%, respectively, at hydraulic loading rate of 0.9 m 3 /(m 2 ·d) under low ambient temperature of −11.5 to 8.0 °C. Effective nitrification, phosphorus-accumulating and organic-degradation were proceeded in the aerobic layers and efficient H2 -/Fe 2+ -mediated autotrophic denitrification and Fe 3+ -based phosphorus immobilization were developed in the anaerobic layers through in-situ H2 -/Fe 2+ -supply by Fe/C micro-electrolysis. AOB (e.g. Nitrosomonadales ), NOB/PAOs (e.g. Nitrospira ), autotrophic denitrificans (e.g. Thiobacillus, Hydrogenophaga and Sulfurimonas ), heterotrophic denitrificans (e.g. Denitratisoma ) and Fe(II)-oxidizing bacteria (e.g. Ferritrophicum ) dominated ME-(O/A)CW and confirmed the reaction mechanisms. The developed ME-(O/A)CW presented significant potential in the practical application for decentralized low-carbon greywater treatment under low ambient temperature.